2023
DOI: 10.1128/mbio.00012-23
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Invasion Is Controlled by Competition among Intestinal Chemical Signals

Abstract: Enteric pathogens acutely sense their environment for signals to regulate their virulence functions. We demonstrate here that the enteric pathogen Salmonella utilizes the competition among certain regional intestinal constituents to modulate its virulence determinants in that region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In addition, many other intestinal factors than the bile content participate in the complex regulatory network of S . Typhimurium intestinal cell invasion, such as intestinal fatty acid and many other small molecules found in the intestine, and interplay with the intestinal microbiota as well (Lou et al, 2019 ; Rogers et al, 2021 ; Chodhury et al, 2021a , b , 2023 ). Thus, further studies are needed to clarify the possible role of other bile molecules and their possible interaction in the invasion process of S .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many other intestinal factors than the bile content participate in the complex regulatory network of S . Typhimurium intestinal cell invasion, such as intestinal fatty acid and many other small molecules found in the intestine, and interplay with the intestinal microbiota as well (Lou et al, 2019 ; Rogers et al, 2021 ; Chodhury et al, 2021a , b , 2023 ). Thus, further studies are needed to clarify the possible role of other bile molecules and their possible interaction in the invasion process of S .…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression was performed as described previously. 24 , 29 , 30 The open reading frame of virF was cloned into pET15b using primers virFpet15 FP/RP and pET15 FP/RP listed in Table 2 , by Gibson assembly. Clones were confirmed by PCR using primers pET15bchk FP/RP and DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The colonic fatty acids are utilized by many enteric pathogens, such as Salmonella , 24 , 29 , 30 Vibrio 31 and enterotoxigenic E. coli , 32 to regulate their virulence programs. Interestingly, all these pathogens induce their virulence programs by the activation of an AraC-type master regulator, such as HilD, HilC and RtsA of Salmonella , ToxT of Vibrio , and Rns of enterotoxigenic E. coli .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that imported and unmetabolized formic acid functions as a cytoplasmic signal that binds to HilD, the master transcriptional regulator of Salmonella invasion, and prevents the repressive fatty acids from binding to the same. Thus, it enhances the lifetime of HilD and subsequent derepression of invasion genes (18). Also, formate utilization by the respiratory formate dehydrogenase-N (FdnGHI) and formate dehydrogenase-O (FdoGHI) are instrumental in the gut colonization by Salmonella .…”
Section: Introductionmentioning
confidence: 99%